Role of vitamin D in endothelial function and endothelial repair in clinically stable systemic lupus erythematosus. (26th February 2015) - Reynolds, John; Ray, David; Alexander, M Yvonne; Bruce, Ian
Abstract: Background: Patients with systemic lupus erythematosus (SLE) have endothelial dysfunction and increased risk of cardiovascular disease. Endothelium-dependent dilatation (ED) is abnormal in patients with SLE, and endothelial repair mechanisms are also impaired. Myeloid angiogenic cells (MACs) promote angiogenesis to restore damaged vessels. Vitamin D deficiency is associated with cardiovascular disease in the general population and is prevalent in SLE. We aimed to assess the effect of vitamin D on endothelial repair and function. Methods: Vitamin D deficient (<20 ng/mL) patients with SLE were treated with cholecalciferol by their physician. Vitamin D replete patients (>30 ng/mL) and healthy controls (>20 ng/mL) were also recruited. Endothelial function was determined by the ratio of ED to independent dilatation (EI). MACs from patients were cultured with and without 10 nM calcitriol, and function determined by migration and angiogenesis assays. Endothelial nitric oxide synthase (eNOS) expression was studied in human aortic endothelial cells treated with tumour necrosis factor α (TNFα) and MAC-conditioned media. Findings: We studied 22 vitamin D deficient and 18 replete patients. Vitamin D deficient patients had an increased number of MACs compared with controls (p=0·04) but impaired migratory capacity (p=0·001) and reduced angiogenic capacity, although this was not statistically significant (p=0·13). Media from calcitriol-treated MACs significantly increased angiogenesis compared with untreated MACs (p=0·01). Calcitriol reduced IP-10 expression by MACs (p<0·0006), and blockade of IP-10 restored the angiogenic capacity of MACs from patients with SLE. In cholecalciferol-treated patients, change in 25-hydroxyvitamin D was strongly correlated with change in ED:EI ( r =0·650, p=0·006) after adjustment for age (odds ratio 1·12, 95% CI 1·02–1·24; p=0·02). Media from calcitriol-treated MACs more strongly attenuated TNFα-mediated downregulation of eNOS in human aortic endothelial cells than did untreated MACs from patients with SLE (p=0·01). Interpretation: In this small experimental study, calcitriol improved endothelial function in patients with stable SLE. This improvement was associated with an increase in MAC number and function. The improved angiogenic capacity in MACs might be mediated via downregulation of IP-10 and changes in ED:EI by MAC regulation of eNOS in endothelial cells. The findings suggest that vitamin D could be a novel therapy to reduce cardiovascular disease in this patient group. Funding: North West England Medical Research Council Fellowship Scheme in Clinical Pharmacology and Therapeutics (funding from UK Medical Research Council (grant number G1000417/94909 ), ICON, Astra Zeneca, GlaxoSmithKline, Medicines Evaluation Unit).